PENERAPAN METODE PLAYWAY MENGGUNAKAN MEDIA GAMBAR DENGAN MATERI BILANGAN CACAH DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 1 MI ZAINUL ANWAR - Umaidah, Avidatul; Anwar Badruttamam, Chaerul; Zahrotul Mufidah, Nani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the use of the playway method with picture media to improve learning outcomes of integer number material in grade 1 students of MI Zainul Anwar. Mathematics, which is important for the development of rational, critical, creative, and innovative thinking, is often considered difficult because it is abstract, while students tend to think concretely. The playway method and image media are considered effective for making learning more fun and easy to understand, especially the concept of small numbers, by connecting numbers and real objects and facilitating learning through play and exploration. Using a descriptive qualitative approach in MI Zainul Anwar (class 1A), this study found that the playway method with picture media increased active participation, motivation, and learning outcomes, as well as making learning more meaningful, fun, and supporting cognitive, social, and motor development.